A further study on the species of the spider genus Leptonetela (Araneae: Leptonetidae) - Wang, Chunxia; Li, Shuqiang (Zootaxa, 2011)
The present paper gives a further study of the spider genus Leptonetela Kratochvíl, 1978. A total of twenty-seven species are reported, including seven known species, thirteen new species, seven new combinations and four new synonyms. Leptonetela kanellisi (Deeleman-Reinhold, 1971), type species for genus, is redescribed based on the specimens from Greece. The new species are: Leptonetela chiosensis sp. nov., L. gittenbergeri sp. nov. from Greece; L. flabellaris sp. nov., L. lineata sp. nov., L. mengzongensis sp. nov., L. mita sp. nov., L. parlonga sp. nov., L. rudicula sp. nov., L. sexdentata sp. nov., L. tianxingensis sp. nov., L. yaoi sp. nov. and L. zhai sp. nov. from China; L. pungitia sp. nov. from Vietnam. The new combinations are: Leptonetela hangzhouensis (Chen et al., 1984) comb. nov. and Leptonetela microdonta (Xu & Song, 1983) comb. nov. transferred from Leptoneta; Leptonetela identica (Chen et al., 2010) comb. nov., Leptonetela lophacantha (Chen et al., 2010) comb. nov., Leptonetela megaloda (Chen et al., 2010) comb. nov., Leptonetela nuda (Chen et al., 2010) comb. nov. and Leptonetela robustispina (Chen et al., 2010) comb. nov. transferred from Qianleptoneta. The new synonyms are: Qianleptoneta lycotropa Chen et al., 2010 is a junior synonym of Leptonetela danxia Lin & Li, 2010; Qianleptoneta triangula Chen et al., 2010 is a junior synonym of Leptonetela digitata Lin & Li, 2010; Qianleptoneta sublunata Chen et al., 2010 is a junior synonym of Leptonetela reticulopecta Lin & Li, 2010 and Qianleptoneta multiseta Chen et al., 2010 is a junior synonym of Leptonetela tetracantha Lin & Li, 2010. In addition, Qianleptoneta palmata Chen et al., 2010 is tranferred to the genus Sinoneta, i.e. Sinoneta palmata (Chen et al., 2010) comb. nov.